Phosphorylated protein component present in influenza virions. - Privalsky, M L (1977)
The nucleoprotein of the WSN strain of influenza was found to be phosphorylated in vitro. The phosphate-protein bond was stable to hot trichloroacetic acid, RNase, DNase, succinic acid, and succinic acid-hydroxylamine, but sensitive to hydrolysis by bacterial alkaline phosphatase. This suggested that the nucleoprotein is in the form of a phosphomonoester. Acid hydrolysis of the isolated nucleoprotein followed by thin-layer electrophoresis identified the phosphorylated amino acid residue as phosphoserine.